2014
DOI: 10.1021/es5005973
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Particulate Matter Emissions from a Current Technology Natural Gas Engine

Abstract: Experiments were conducted to characterize the particulate matter (PM)-size distribution, number concentration, and chemical composition emitted from transit buses powered by a USEPA 2010 compliant, stoichiometric heavy-duty natural gas engine equipped with a three-way catalyst (TWC). Results of the particle-size distribution showed a predominant nucleation mode centered close to 10 nm. PM mass in the size range of 6.04 to 25.5 nm correlated strongly with mass of lubrication-oil-derived elemental species detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 31 publications
7
35
2
Order By: Relevance
“…In contrast to a previous study that reported that the majority of PM mass was due to fuel and oil additive species such as magnesium (Mg) and calcium (Ca) [36], these accounted for small fractions of total PM (<5 %) in this evaluation. Sodium and sulfate were still the dominant species emitted from the CNG engine, and except for sodium during the Near-Dock Drayage route (1.89 of 12.4 mg/mi), they remained relatively constant among routes.…”
Section: Speciation Of Pm Emissions By Iccontrasting
confidence: 99%
“…In contrast to a previous study that reported that the majority of PM mass was due to fuel and oil additive species such as magnesium (Mg) and calcium (Ca) [36], these accounted for small fractions of total PM (<5 %) in this evaluation. Sodium and sulfate were still the dominant species emitted from the CNG engine, and except for sodium during the Near-Dock Drayage route (1.89 of 12.4 mg/mi), they remained relatively constant among routes.…”
Section: Speciation Of Pm Emissions By Iccontrasting
confidence: 99%
“…575). For example, Thiruvengadam et al (2014) and Eichler et al (2017) have suspected engine lubricating oil to be responsible for a large portion of engine-emitted particles. Therefore, we believe that also lubricating oil is a potential candidate for the source of secondary aerosol.…”
Section: Instrumentation and Data Analysismentioning
confidence: 99%
“…Typically, volatile species contain sulphates, nitrates, and organic elements and non-volatile species contain a carbonaceous fraction and ash. The organic fraction contains thousands of compounds including esters, alkenes, ketones, aromatics, and alcohols [41]. The sulphate fraction includes sulphate ions (SO 4 2− ), sulphuric acid (H 2 SO 4 ), and water-soluble sulphates; however, H 2 SO 4 covers the major proportion of this fraction.…”
Section: Particle Compositionmentioning
confidence: 99%